Broadband transparent metamaterial absorber in wireless communication band based on indium tin oxide film. Issue 12 (4th September 2019) - Yu, Buyun; Zhao, Yongjiu; Chen, Jiaqing; Ge, Yue; Chen, Xiaofeng
Abstract: In this article, a broadband optically transparent metamaterial absorber in wireless communication band is proposed. Indium tin oxide (ITO) film, a kind of resistive transparent thin film, is utilized to construct the absorber unit to realize optical transparency, and increase ohmic loss to broaden the absorption bandwidth. The proposed absorber is fabricated and measured. The measurement results are in good agreement with the simulations. It is demonstrated that the absorption rate of the proposed absorber is higher than 90% from 1.67 to 3.8 GHz. The full width at half maximum bandwidth is 5.11 GHz from 0.89 to 6 GHz. In addition, the absorption response of the absorber remains stable regardless of polarization and incidence angle of the electromagnetic waves.